Penerapan Model Pembelajaran Discovery Learning Dalam Meningkatkan Hasil Belajar Matematika - Sianturi, Darwin (JURNAL GLOBAL EDUKASI, 2020)
Abstrak: The purpose of this study was to determine the application of the Discovery Learning learning model to improve student learning outcomes on the subject of the Equation of Tangent Circles in SMA Negeri 1 Siborongborong in the 2019/2020 academic year. This research is a classroom action research with the research subjects of class XI students of SMA Negeri 1 Siborongborong, amounting to 39 people. The instrument used was a test consisting of 5 items. From the research results from the first cycle, it was found that the number of students who obtained individual completeness was 28 people (71.79%), with an average value of 71.21. The results of observations in the first cycle found that the percentage of student activity was 65% or in the good category. The action results in cycle II obtained that the number of students who obtained individual completeness was 39 people (100%) with an average value of 80.15. The observation result in cycle II showed that the percentage of student activity was 85% or in the good category. From the results of the actions in cycle I and cycle II, it is concluded that the application of the Discovery Learning learning model can improve student learning outcomes in the material of the Equation of Tangent Circles in SMA Negeri 1 Siborongborong in the 2019/2020 academic year. Kata kunci: circle; discovery learning; tangent Abstrak: Tujuan penelitian ini adalah untuk mengetahui penerapan model pembelajaran Discovery Learning dapat meningkatkan hasil belajar siswa pada pokok bahasan Persamaan Garis Singgung Lingkaran di SMA Negeri 1 Siborongborong tahun pelajaran 2019/2020. Penelitian ini merupakan penelitian tindakan kelas, dengan subjek penelitian siswa kelas XI SMA Negeri 1 Siborongborong yang berjumlah 39 orang. Instrumen yang digunakan adalah tes yang terdiri dari 5 butir soal. Dari hasil penelitian dari siklus pertama diperoleh jumlah siswa yang memperoleh ketuntasan secara individu sebanyak 28 orang (71,79%) dengan nilai rata-rata sebesar 71,21. Hasil observasi pada siklus I diperoleh bahwa persentase aktivitas siswa sebesar 65% atau berada pada kategori cukup. Hasil tindakan pada siklus II diperoleh jumlah siswa yang memperoleh ketuntasan secara individu sebanyak 39 orang (100%) dengan nilai rata-rata sebesar 80,15. Hasil observasi pada siklus II diperoleh bahwa persentase aktivitas siswa sebesar 85% atau berada pada kategori baik. Dari hasil tindakan pada siklus I dan pada siklus II maka disimpulkan penerapan model pembelajaran Discovery Learning dapat meningkatkan hasil belajar siswa pada materi Persamaan Garis Singgung Lingkaran di SMA Negeri 1 Siborongborong tahun pelajaran 2019/2020. Kata kunci: discovery learning; garis singgung; lingkaran